2020
DOI: 10.1103/physrevresearch.2.023055
|View full text |Cite
|
Sign up to set email alerts
|

Inverse spin Hall effect induced by asymmetric illumination of light in topological insulator Bi2Se3

Abstract: Using circularly polarized light is an alternative to electronic ways for spin injection into materials. Spins are injected at a point of the light illumination, and then diffuse and spread radially due to the in-plane gradient of the spin density. This diffusion is converted into a circular charge current by the inverse spin Hall effect (ISHE). With shining the circularly polarized light at asymmetric parts of the sample, such as near edges, we detected this current as a helicity-dependent component in the ph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Here, we characterize this additional effect, and we find a solution for correcting the results. Our findings are relevant for experiments where the circularly polarized focused beam is used to probe locally the helicitydependent properties [19][20][21][22][23][24]26,29,31,34 , as the thermal gradients create similar signals. Furthermore, for experiments using a fixed circularly polarized beam 18,25,27,28,30,32,33,[36][37][38] , the beam deflection associated to the helicity reversal may slightly modify the illumination conditions and also influence the results.…”
mentioning
confidence: 75%
See 3 more Smart Citations
“…Here, we characterize this additional effect, and we find a solution for correcting the results. Our findings are relevant for experiments where the circularly polarized focused beam is used to probe locally the helicitydependent properties [19][20][21][22][23][24]26,29,31,34 , as the thermal gradients create similar signals. Furthermore, for experiments using a fixed circularly polarized beam 18,25,27,28,30,32,33,[36][37][38] , the beam deflection associated to the helicity reversal may slightly modify the illumination conditions and also influence the results.…”
mentioning
confidence: 75%
“…It has been shown that circularly polarized 15 light can induce the magnetization reversal 5,16 as well as produce photovoltaic or photoresistive effects 17,18 . The changes of photoresistance [19][20][21][22][23][24][25] or photocurrent 24,[26][27][28][29][30][31][32][33][34][35][36] have been attributed to the interaction between light and spin accumulation. This type of effect appears to be "universal", as it has been observed in semiconductors 24,27 , semimetals 25,37 , topological insulators [29][30][31][32][33][34][35][36] , normal metals 19,20 and even complex metalorganics structure 38 .…”
mentioning
confidence: 99%
See 2 more Smart Citations